The landscapes of China: past and present influences on society and politics - Veeck, Gregory (Henry Stewart Talks, 2013)
Chinese economy, Uneven landscape, East-West stairs, China's topography, Physical features, Annual precipitation, China's rivers, Chinese dominion in Central Asia and trade, Western trade routes, Trade in its historical context, Value of West China, Population distribution, Railways, Rural per capita income, Migration patterns, Fuels, power, minerals, metals, Develop the west initiative, Eurasian pipeline, High-speed rail, Comparison of China's regions, Rural per capita change, National integration